Studying the clinical profile of blunt hepatic trauma - Pal, Vijay; Arora, Bhavinder Kumar; Singh, Rohit; Mittal, Gourav; Shekhawat, Monika; Garg, Neha; Sirohi, Vivek (International Surgery Journal, 2021)
Background: The liver is the largest intra-abdominal organ and is considered to be the second commonest organ to be injured in blunt abdominal trauma. Blunt hepatic injuries due to road traffic accidents are the sixth leading cause for death in India. Approximately 15-20% of abdominal injury presents as hepatic trauma and is liable for 50% of death resulting from abdominal trauma. The mortality rate is higher with blunt hepatic trauma than penetrating injuries. The advent of improved and expeditious imaging technologies amid advances in critical-care monitoring, prompted a significant shift towards conservative management of solid-organ abdominal injuries. Methods: The study was conducted over 96 patients in General Surgery Department, PGIMS, Rohtak with a history of blunt hepatic injury. The study duration was from 16th May 2018 till 1st June 2020. The aim of the study was to evaluate the pattern of blunt hepatic trauma and the patterns with which they presented in the emergency department. Results: In this study, 98.96% of the patients were managed conservatively whereas only 1.04% of patients needed surgical intervention. Conservative approach was possible because of strict patient monitoring, availability of experienced surgeons and radiologists, good intensive care unit care. Conclusions: The study concluded that conservative management of the patient is better than operative management and can be done in the patients who are hemodynamically stable. Most of the patients settle after 48 hours if managed conservatively.